BRAND EXPERIENCE, ATTITUDE, AND LOYALTY IN BRAND EQUITY FASHION LUXURY BRAND - Fanandaru, Esti Mulya; Kurniawati, Kurniawati; Wahyuni, Nofi; Septiani, Yunita (International Journal of Application on Economics and Business, 2023)
Luxury products have become a means of self-actualization in society to show prosperity or wealth. Even so, the consumption of luxury goods is the prerogative of people in the world. There are several studies and research that discuss this luxury item to understand how consumer experiences with brands are either negative or positive, how luxury products affect people's attitudes which ultimately lead to loyalty to product purchases and provide benefits to producers how the product is considered good by the public. The purpose of this paper is to find out how the influence of brand experience, brand attitude, and brand loyalty on brand equity in luxury fashion brands. The research method used in this study is collecting responses from consumers who have at least bought several luxury fashion brands (such as Hermes, Chanel, Yves Saint Laurent, Fendi, and other luxury fashion brands with a minimum of 2 purchases within 2 years. Data were collected from 188 respondents using a questionnaire with a Likert scale. The empirical results show that customer engagement positively encourages brand loyalty.